The Nectarine Pit as a Cause for Small Bowel Obstruction and Perforation: A Case Report. (27th March 2013) - Al-Najjar, Mahmoud; Arthur, Thomas
Abstract : Ingestion of a foreign body is a rare cause of small bowel obstruction. Ingested foreign bodies will usually pass without clinical sequelae, however on occasion can contribute to significant morbidity. Here we present an unusual case of small bowel obstruction and perforation as a result of accidental ingestion of a nectarine pit.